Intervensi Mengontrol Nyeri dan Ansietas Pada Pasien dengan Sindrom Koroner Akut - Luciana Kabang; Elly Nurachmah; I Made Kariasa (Journal of Telenursing (JOTING), 2023)
This literature study aims to identify complementary therapies that can be used to reduce pain and anxiety in patients with acute coronary syndrome. The research method uses literature study, articles collected through the Google Scholar, EBSCO, Science Direct, Scopus and ProQuest databases in the form of articles published in 2018-2022 using the PRISMA approach. The article search strategy uses keywords/MeSH, namely "Complementary therapy" AND "Nursing Intervention" AND "Pain" AND "anxiety" AND "Acute Coronary Syndrome". As a result of the research, a total of 9 articles containing complementary therapy interventions in controlling pain were selected based on the inclusion criteria of patients with a medical diagnosis of acute coronary syndrome and were human clinical trials. In conclusion, inhalation of aromatherapy Melissa essential (lemon balm) and peppermint as well as thermotherapy are effective in the patient's acute pain phase. Deep breathing and massage relaxation interventions can reduce anxiety in ACS patients. Key words: Anxiety, Pain, Acute Coronary Syndrome, Complementary Therapy